MACROPROLACTINOMA PRESENTING WITH PITUITARY APOPLEXY: A CASE REPORT AND LITERATURE REVIEW - Wongkumpan, Thaniya (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 59-year-old female with no illness or medications presented with a thunderclap headache and bitemporal hemianopia for one week. Visual acuity was reduced to finger counting OS. MRI revealed a 2 x 3 x 3 cm cystic-solid lesion with internal hemorrhage at the sellar-suprasellar region with superior displacement of optic chiasm and optic tract. Tests showed serum prolactin 209.9 ng/mL [1:100 dilution, 72% recovery after PEG precipitation (reference >60%)]; normal TSH; and low FT4, IGF-I, FSH and serum cortisol, consistent with pituitary macroadenoma with apoplexy, optic chiasm and optic nerve compression, central hypothyroidism, secondary adrenal insufficiency and hyperprolactinemia from stalk effect. Endoscopic endonasal surgery revealed a blood clot. Visual symptoms did not improve. Post-operative serum prolactin was 213 ng/mL. She was treated as a pituitary neuroendocrine tumor (PitNET) with PIT1 lineage of lactotroph tumors which express dopamine D2 receptor. She was managed medically with a dopamine agonist.